2007
DOI: 10.1007/s00441-006-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane protein distribution in LYVE-1-immunoreactive lymphatic vessels of normal tissues and ovarian carcinomas

Abstract: The endothelial cells of blood vessels assemble basement membranes that play a role in vessel formation, maintenance and function, and in the migration of inflammatory cells. However, little is known about the distribution of basement membrane constituents in lymphatic vessels. We studied the distribution of basement membrane proteins in lymphatic vessels of normal human skin, digestive tract, ovary and, as an example of tumours with abundant lymphatics, ovarian carcinomas. Basement membrane proteins were loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…Although the authors attributed the effect to secreted laminin-421, the medium appeared to contain α5-laminins and probably both laminins 411 and 421, and the authors erroneously used mAb 22 to the LMγ1chain (B2 chain in the early nomenclature) to demonstrate the presence of the laminin β2 chain in the medium. In vivo, lymphatic endothelium expresses the laminin α4, β1, β2, γ1, and sometimes α5 chains (Vainionpää et al, 2007a). In an additional study, glomerular mesangial cells, which express both laminins 411 and 421, selectively used endogenous laminin-421 and α6β1 integrin to migrate following stimulation with IGFBP-5 (Berfield et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the authors attributed the effect to secreted laminin-421, the medium appeared to contain α5-laminins and probably both laminins 411 and 421, and the authors erroneously used mAb 22 to the LMγ1chain (B2 chain in the early nomenclature) to demonstrate the presence of the laminin β2 chain in the medium. In vivo, lymphatic endothelium expresses the laminin α4, β1, β2, γ1, and sometimes α5 chains (Vainionpää et al, 2007a). In an additional study, glomerular mesangial cells, which express both laminins 411 and 421, selectively used endogenous laminin-421 and α6β1 integrin to migrate following stimulation with IGFBP-5 (Berfield et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The laminin α4 chain, originally cloned in human and shortly thereafter in mouse (Richards et al, 1994(Richards et al, , 1996Iivanainen et al, 1995Iivanainen et al, , 1997Liu and Mayne, 1996;Friesser et al, 1997), constitutes a truncated α chain with a size of nearly 200 kDa. α4-laminins, such as 411 (formerly laminin-8), 421 (formerly laminin-9), and 423 (formerly laminin-14), are expressed by vascular and lymphatic endothelial cells, smooth muscle cells, mesangial cells, pericytes, fibroblasts, platelets, leukocytes and other cells of mesenchymal origin (Miner et al, 1997;Friesser et al, 1997;Geberhiwot et al, 1999Geberhiwot et al, , 2001Pedraza et al, 2000;Talts et al, 2000;Libby et al, 2000;Petäjäniemi et al, 2002;Hansen and Abrass, 2003;Matsuura et al, 2004;Wondimu et al, 2004;Fried et al, 2005;Vainionpää et al, 2007a). Laminin-411 is recognized by α6β1 and probably also α3β1, α6β4, and αVβ3 integrins and promotes adhesion and/ or migration of several cell types as well as neurite outgrowth (Geberhiwot et al, 1999(Geberhiwot et al, , 2001Kortesmaa et al, 2000;Pedraza et al, 2000;Talts et al, 2000;Gonzales et al, 2001Gonzales et al, , 2002Wondimu et al, 2004;Fried et al, 2005;Lian et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By immunofluorescence study, Fiedler et al detected that CD-34-positive vessels were LYVE-1 + /Prox-1 + /lymphatic vessels in peritumoral and intratumoral colonic tissue from patients with colonic carcinoma [12]. Lymphatic vessels are readily identifiable by immunocytochemical staining as follows: (1) D2-40 [1,2]; (2) podoplanin, a 43-kDa glycoprotein cloned as a cell-surface protein expressed on glomerular podocytes [3,11]; (3) LYVE-1 [5][6][7]13]; (4) Prox-1, a transmembrane factor, that is expressed in lens, heart, liver, and nervous system [14]; (5) vascular endothelial growth factor-receptor 3 (VEGF-R3), a receptor tyrosine kinase, that is mainly expressed on lymphatic vessels [15]; and (6) desmoplakin, present in endothelial adhering junction, that is immunostained in small lymphatic vessel endothelium [16]. Thus, lymphatic vessels comprise a complex vascular system as characterized by many markers, as listed above.…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies for quantitative analysis using LYVE-1 RNA reported below-detectable levels of LYVE-1 RNA in normal colon [4]. Thus, we aimed to immunocytochemically identify lymphatic vessels in normal colon, polyps, and adenomas using polyclonal antihuman LYVE-1 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…11 Intriguing recent data show that Lu expression is enhanced in various carcinomas and during malignant transformation of epithelial cells, pointing to a possible role in cancer biology. [12][13][14][15] To better understand Lu receptor function(s) in both normal and pathologic states, we are investigating the structural interactions of these transmembrane proteins.The 2 Lu isoforms (85 and 78 kDa) 16 are members of the immunoglobulin superfamily (IgSF). 11 The 85-kDa Lu glycoprotein contains 5 disulfide-bonded extracellular IgSF domains, a single hydrophobic membrane span, and a cytoplasmic domain of 59 residues.…”
mentioning
confidence: 99%